Sudan prices and availability monitoring survey (SPAMS): Methodology, coverage, and value addition - Rakhy, Tarig; Siddig, Khalid (International Food Policy Research Institute, 2026)
Sudan is facing profound economic and market disruptions driven by prolonged conflict, political instability, and severe macroeconomic deterioration. These shocks have substantially undermined agricultural production, disrupted supply chains, and weakened market functioning across the country. Agriculture, which remains central to livelihoods, food security, and economic activity in Sudan, has been particularly affected by infrastructure damage, population displacement, rising input and transport costs, and increasing fragmentation of markets. In this context, food availability and affordability have become highly volatile, with wide spatial disparities across states and localities.